A experiência de internamento em UTI devido à Covid-19: ressonâncias na existência do paciente. - Macêdo, Maria Paula Marques (2023)
The present study aimed to understand the experience of hospitalization in the ICU of patients affected by covid-19 and the resonances in each existence, taking as a sparing point some of the hermeneutic phenomenological assumptions about the reality and the phenomenon of illness. For that, the narrative interview and the researcher's field diary were used as resources. Four collaborators participated in the interviews, who were hospitalized in the ICU of covid-19 in different hospitals in the city of Recife. The meetings were held about two months after being discharged. The nature of the present research is qualitative, guided by hermeneutic phenomenological assumptions, resonant with Heidegger's Existential Analytics hospitalization in an Intensive Care Unit is a factual event that imposes ruptures, which may reveal multiple meanings to resonate uniquely in each existence. In general, we sought to reflect on the impacts of the interrogated experience, considering the experience, moving away from understandings that are limited to the experience of illness in terms of diagnosis and treatment. From such horizons, the internment experience was revealed as a crisis mobilizer, opening wide the unpredictability of existing and launching the human into indeterminacy. In this direction, too, it was pointed to the "uncovering" of the original condition of the human being as a finite being, which takes place from the awakening of the fundamental affective tone of anguish. Such understandings also point to the mastery of a technicist look at the hospitalization situation, a perspective that governs the health context but ends up leaving aside the patient's experience. In this direction, it was possible to understand that technical doing has a place and is necessary for such a context. However, it is also essential to look at the reception and legitimation of the experience of those who are sick.